Relationship of Determined Risk Factors with Hearing Disorders in Children - Oziel González Milián; María Felicia Casanova González; Yaima Figueredo Montes de Oca (Revista Finlay)
Foundation: studying risk factors, which contribute to the appearance of deafness, is a need so that prophylactic and preventive control can be developed during the prenatal, perinatal and postnatal periods. Objective: to determine the association of certain risk factors with hearing loss in children. Method: correlational cross-descriptive study at the University Pediatric Hospital Paquito González Cueto de Cienfuegos, from May the 2nd 2016 to May the 1st 2016. A number of 149 patients were studied with present risk factors of hearing loss, who were referred and attended the consultation at the neuro-physiology department of the pediatric hospital. Descriptive statistic calculations were done with absolute and relative frequency of variables. The relationship of the determined risk factors, with the result of hearing sift, by Odd ratio confidence interval of 95 %. A data base was designed in SSPS 1.5 statistic package for data processing. The obtained data were presented in tables. Results: hearing loss was detected in 14.1 % of the studied cases. A relation statistically significant was found among some risk factors with an abnormal result of the hearing shift. Conclusion: risk factors, which were related with hearing loss, were: fetal suffering, use of ear toxic drugs in the child and malformations of face or neck.